Comparative analysis of LQR and robust controller for active suspension - Mohamad, Kaleemullah; Faris, Waleed Fekry; Rashid, Muhammad Mahbubur; Hasbullah, F. (Inderscience Publishers, 2012)
This paper aims to investigate the performance of linear quadractic regulator (LQR), robust H∞ and passive controller for active suspension of the quarter car model. The presented approach is based on linear model well supported by computer-aided control systems design (CACSD) tool which yields faster control design approach. The linear active suspension provides better handling and ride comfort by suppressing the vibration induced due to road disturbance. Road disturbance was added to check the vibration limitation by these controllers. Results were evaluated in both the frequency domain and the time domain. The results show the impact of active suspension techniques on vehicle dynamics and passenger comfort and handling.